Implementation of Information Technology, Opportunity, and Tendency of Fraud - Nurlita Novianti; Yuki Firmanto (Association of Certified Fraud Examiners Indonesia Chapter, 2022)
The research investigates the impact of fraud in Indonesian public sector by using information technology phenomenon. The study investigates the impact of information technology on the tendency of fraud through mediation to construct an opportunity. Based on the logical thinking of information technology provides capabilities for companies that could potentially open up an opportunity for fraud perpetrators to commit fraud. Therefore, the first test of the research examines the effect of information technology to construct an opportunity. The second test, the research explores the information technology that influence the tendency of fraud without mediation to construct an opportunity. The research uses a group of 58 person who experienced in finance and procurement departments using the judgment sampling method. Partial Least Squares was used to analyze the data. The findings indicate that the existence of information technology within an agency to provide the benefits of information technology capability that was conceived as a media and, therefore, information technology capability will also be able to provide a loophole for fraud perpetrators to do fraud.